Calvin the preacher: His explanation of the doctrine of predestination in the sermon of 1551 and in the Institutes of 1559 - Neuser, Wilhelm H. (Hervormde teologiese studies, 1998)
In this study, Calvin 's famous sermon on eternal election of 1551 is dis-cussed and compared to his treatment of the doctrine in his Institutes, 1559. This is a necessary study, never undertaken before, of the correlation between Calvin's pastoral treatment of the Biblical doctrine of predestination and his more didactic-apologetic approach in the Institutes. Here the main argument in the sermon is summarised and, at every point, the corrsponding passage in the Institutes is also discussed and the difference in approach and argument evaluated. In this way a more complete knowledge of Calvin's understanding of this doctrine is gained. To assist the reader, the text of the sermon of 1551 is also published. The final conclusion is that the sermon is a valuable addition to the Institutes. Without it, Calvin's pastoral treatment of the doctrine is ignored when evaluating his exposition on eternal election.